TINJAUAN YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 90/PUU-XXI/2023 TERKAIT PERSYARATAN CALON PRESIDEN DAN CALON WAKIL PRESIDEN DIKAITKAN DENGAN ASAS PEMBAGIAN KEKUASAAN - Sahara, Iman Fadilah Erian; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The 1945 Constitution (UUD 1945) is one of the sources of Indonesianlaw. The age limit is stated in Article 169 letter q of Law Number 7 of 2017concerning Elections so it is felt to be inappropriate because the ConstitutionalCourt is a judicial institution or negative legislator, which means it does notimmediately make new rules and add legal norms to Law Number 7 2017concerning General Elections. The Constitutional Court has no authority toreplace or insert new norms into the content (paragraphs, articles and/or parts)of laws that have been declared contrary to the 1945 Constitution and thereforedo not have binding legal force.This type of legal research can be categorized as using a normative type oflegal research. Normative legal research is library legal research. The datasources used are secondary data consisting of primary legal materials, secondarylegal materials and tertiary legal materials. The data collection technique comesfrom the library research method. After the data is collected, conclusions aredrawnFrom the results of the research, 2 (two) main things were obtained,namely first, even though a judicial tip occurred, a criminal act or violation of thecode of ethics committed by a judge, does not make the Constitutional Court'sdecision invalid or wrong. Second, in this case the role of the ConstitutionalCourt is as a judicial institution which has the task of examining laws that arealready in force or that have been passed.Keyword: Constitutional Court, Ethics, Conflict of Interest